Can the Erga Omnes Principle Revolutionize State Administrative Courts? A Challenge Through Lawrence M. Friedman’s Legal System Theory - Mayaka, Raphael Bertrand; Sulistiyono, Tri; Gusthomi, Moh. Imam; Windiahsari, Windiahsari (Universitas Negeri Semarang, 2024)
The principle of erga omnes, which signifies obligations binding on all parties, has traditionally been associated with international law and human rights. However, its application within state administrative courts remains an underexplored and provocative area of legal theory. This study delves into whether the erga omnes principle can be adapted to revolutionize Indonesia’s State Administrative Court (PTUN) system, drawing on Lawrence M. Friedman’s Legal System Theory as a framework. Friedman’s theory, which emphasizes the interaction of legal rules, legal culture, and the legal environment, offers an insightful lens to analyze the broader implications of applying erga omnes in the domestic administrative context. The findings suggest that while the erga omnes principle could significantly strengthen the role of state administrative courts in ensuring broader societal justice, its implementation presents notable challenges. These challenges include the difficulty in aligning domestic legal systems with the universal and binding nature of erga omnes, the risk of overwhelming courts with cases that require systemic change, and the potential for conflicting interpretations of the principle's scope. Despite these challenges, the study proposes that strategically applying erga omnes could enhance legal coherence, public trust, and accountability in administrative decision-making. This research challenges conventional thinking by proposing an audacious application of international legal principles to domestic administrative law. It provides fresh insights into how judicial reform could reshape the PTUN system, urging policymakers and legal scholars to rethink the boundaries of state administrative justice in Indonesia.